Risk of Remote Seizures After Perinatal Ischemic Stroke - David G. Ritacco (Pediatric Neurology Briefs Publishers, 2016)
Investigators from the University of California San Francisco and Kaiser Permanente Medical Centers in Oakland report outcome of perinatal arterial ischemic stroke (PAIS) in a population-based cohort, with particular attention to the incidence of seizures.